Revision of the fish family Euclichthyidae (Pisces: Gadiformes) with the description of two new species from the Western Pacific - Last, Peter R.; Pogonoski, John J. (Zootaxa, 2020)
Members of the benthopelagic fish family Euclichthyidae, also known as the Eucla cods, occur on the upper continental slopes off Australasia at 220–1040 m depths. Euclichthyids essentially differ from other gadiform fishes in a combination of two almost contiguous dorsal fins with the second much longer based, a deeply notched anal fin with its anterior portion greatly elevated, jugular pelvic fins consisting of 3 partly united filiform upper rays and 3 free filamentous lower rays, an asymmetrical caudal fin with 5 hypurals fused into two plates, and no chin barbel, or vomerine and palatine tooth patches. Additional characters attributed to the group by other published studies include: no horizontal diaphragm within the posterior chamber of the swim bladder, no swim bladder-auditory capsule connection, presence of a luminous organ, and cranial muscle adductor arcus palatini divided by a strong ligament running from the lateral ethmoid and palatine to the medial face of the hyomandibular. Widely considered to be monotypic since its erection in 1984, the group consists of a single genus and three allopatric species, Euclichthys polynemus McCulloch, 1926 (Western and southern Australia, New Zealand), and two new taxa, E. microdorsalis sp. nov. (northeastern Australia) and E. robertsi sp. nov. (eastern Australia and New Caledonia). Eucla cods are morphologically conservative with both new species superficially resembling the type species, E. polynemus. Euclichthys microdorsalis sp. nov. is the most anatomically and morphologically divergent member of the group in having a shorter first dorsal fin, longer snout, relatively small eye compared to its interorbital width, and fewer caudal-fin rays and primary rakers on the outer gill arch than its congeners. Euclichthys robersti sp. nov. differs from E. polynemus in being smaller with a more slender head, and having a smaller eye, longer anal-fin base and tail, smaller scales, fewer primary rakers on the outer gill arch, more elongate oval otoliths, and usually having a X and/or Y bone in the caudal skeleton (both absent in other Euclichthys). Little is known of their biology but available material suggest that early juveniles remain pelagic in the open ocean with adults benthopelagic near the sea floor. Diagnoses and a key are provided for the three species.